Implementation of the Merdeka Belajar Kampus Merdeka Theori Freire Program - Dina Gasong; Normalia Sirande (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Learning that prioritizes freedom of expression, smart in socializing, and virtuous becomes the principle of independent Learning Program. This principle has been introduced by Paulo Freire, which is also in line with the principles of Constructivism. The purpose of this study was to describe the effectiveness of the implementation of the independent Learning Independent Campus (MBKM) program for UKI Toraja students. The research method applied is a qualitative approach, with data collection techniques through open questionnaires to students. The implementation phase of the research started from the registration of MBKM programming students, followed by sending an open questionnaire to interns at the South Sulawesi Language Center by applying the principle of Independent Learning according to a constructivist approach. The second stage is to classify the results of the questionnaire from students, then discuss the results of the questionnaire, by linking the results of the questionnaire with the constructivist approach, and Paulo Freire's theory. To determine the validity of the data, triangulation was carried out to students regarding the results of the questionnaire. This research was conducted in the even semester of 2021/2022, for UKI Toraja students in 2019. The results showed that the Independent Learning Campus (MBKM) was effective in developing creativity, independence, and social interaction. Based on the results of this study, it is recommended for further researchers to examine aspects of personal communication in the implementation of the Independent Learning Campus (MBKM) program